The impact of serum uric acid on psoriasis: NHANES 2005–2014 and Mendelian randomization - Hu, Minghui; Wang, Yangyang; Xu, Wenwu; Bai, Juan; Tang, Xingming (Frontiers in Genetics, 2024)
Background: Psoriasis is a chronic systemic inflammatory disease, and hyperuricemia is a common comorbidity in patients with psoriasis. However, the exact relationship between uric acid levels and psoriasis remains unclear. This study aimed to explore the association between uric acid levels and psoriasis. Methods: Observational study participant data (≥16 years, n =23,489) from NHANES 2003-2014. We conducted analyses using a weighted multiple logistic regression model. Genetic data sets for uric acid levels and psoriasis were obtained from the IEU database. We selected genetically independent loci closely associated with serum uric acid levels as instrumental variables and performed Mendelian randomization analyses using five complementary methods: inverse variance weighting (IVW), MR-Egger, weighted median, simple mode, and weighted mode. Results: After adjusting for other covariates, the results revealed no significant association between serum uric acid levels and psoriasis (b=0.999, 95% CI: 0.998, 1.001, p=0.275). Subgroup analyses stratified by gender and ethnicity showed no significant association between sUA and psoriasis in any of the subgroups. Furthermore, the MR analysis involved the selection of 227 SNPs that were associated with both sUA and psoriasis. IVW results demonstrated no causal relationship between sUA and psoriasis (OR = 0.282, 95% CI: -0.094-0.657, p=0.142). Conclusions: Our study suggests that uric acid levels are not significantly causally related to psoriasis. This finding provides valuable insights for the treatment and prevention of psoriasis, indicating that merely reducing uric acid levels may not be an effective strategy to reduce the risk of psoriasis onset.